Effect of hexyloxy position on antagonistic properties of KH-5 (1-{2-[4-(hexyloxy)benzoyloxy]ethyl}-1-methyl-1,2,3,6-tetrahydropyridin-1-ium iodide) at muscarinic acetylcholine receptors - Janoušková-Randáková, Alena; Mezeiová, Eva; Bláhová, Jana; Chetverikov, Nikolai; Dolejší, Eva; Nelic, Dominik; Prchal, Lukáš; Novák, Martin; Korábečný, Jan; Jakubík, Jan (Biomedicine & pharmacotherapy, 2025)
Antagonists with a long residence time at the receptors are desired for the possibility of reducing daily doses and side effects. KH-5 (1-{2-[4-(hexyloxy)benzoyloxy]ethyl}-1-methyl-1,2,3,6-tetrahydropyridin-1-ium iodide) is the long-acting M1-preferring bitopic muscarinic antagonist with a half-life at muscarinic receptors of up to five hours. The binding of 2-hexyloxy and 3-hexyloxy analogues of KH-5 was simulated in silico, compounds were synthesized and their binding and antagonistic properties were measured experimentally in CHO cells expressing individual subtypes of muscarinic acetylcholine receptors. The overall binding affinities of the new compounds were similar to their respective parent compounds. Shifting the hexyloxy chain to ortho and meta positions led to a decrease in potency at the M1 receptor but an increase in potency at the M2 receptor and abolition of long-term antagonism. Preservation of the para position of the hexyloxy chain is essential for the further development of M1-preferring antagonists. Modifications of the basic centre may be the way to improve the geometry of antagonists towards long residence times to obtain the desired long-acting muscarinic antagonists in the future. The additional challenge for further development is the low metabolic stability of compounds.
Keywords: antagonisté muskarinových receptorů; CHO buňky; receptor muskarinový M1; Receptors, Muscarinic; receptory muskarinové; Pyridines; pyridiny; zvířata; vztahy mezi strukturou a aktivitou; CHO Cells; Structure-Activity Relationship; Receptor, Muscarinic M1; Cricetulus; Muscarinic Antagonists; Animals